Detection of thiol-based redox switch processes in parasites - facts and future - Rahbari, Mahsa; Ulrich, Kathrin; Becker, Katja; Krauth-Siegel, Renate; Jortzik, Esther (Biological chemistry, 2015)
Abstract Malaria and African trypanosomiasis are tropical diseases caused by the protozoa Plasmodium and Trypanosoma, respectively. The parasites undergo complex life cycles in the mammalian host and insect vector, during which they are exposed to oxidative and nitrosative challenges induced by the host immune system and endogenous processes. Attacking the parasite’s redox metabolism is a target mechanism of several known antiparasitic drugs and a promising approach to novel drug development. Apart from this aspect, oxidation of cysteine residues plays a key role in protein-protein interaction, metabolic responses to redox events, and signaling. Understanding the role and dynamics of reactive oxygen species and thiol switches in regulating cellular redox homeostasis is crucial for both basic and applied biomedical approaches. Numerous techniques have therefore been established to detect redox changes in parasites including biochemical methods, fluorescent dyes, and genetically encoded probes. In this review, we aim to give an insight into the characteristics of redox networks in the pathogens Plasmodium and Trypanosoma, including a comprehensive overview of the consequences of specific deletions of redox-associated genes. Furthermore, we summarize mechanisms and detection methods of thiol switches in both parasites and discuss their specificity and sensitivity.